2007
DOI: 10.1016/j.joca.2007.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of labral tears and cartilage loss in patients with mechanical symptoms of the hip: evaluation using MR arthrography

Abstract: Labral tears and cartilage loss are common in patients with mechanical symptoms in the hip. Cartilage loss, labral tears and BME appear interrelated and may represent important risk factors that may affect the development and progression of osteoarthritis in the hip joint.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
89
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(95 citation statements)
references
References 24 publications
3
89
1
2
Order By: Relevance
“…Based on our findings, SHOMRI scoring of the hip is a precise and reliable method to evaluate hip cartilage and labral abnormalities. MRI has been shown to be highly sensitive and specific for characterization and assessment of musculoskeletal disorders [19][20][21][22][23] and especially in the setting of joint pathologies several MR-based scoring methods have been introduced [11,19,[24][25][26][27][28], all with the common purpose to provide practice guidelines in describing and quantifying radiologic findings and to minimize subjectivity. Moreover, the accurate and systematic classification of MRI using a standardized terminology of reporting creates reproducibility that is ideally reflected in high intra-and interrater reliability of each method.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on our findings, SHOMRI scoring of the hip is a precise and reliable method to evaluate hip cartilage and labral abnormalities. MRI has been shown to be highly sensitive and specific for characterization and assessment of musculoskeletal disorders [19][20][21][22][23] and especially in the setting of joint pathologies several MR-based scoring methods have been introduced [11,19,[24][25][26][27][28], all with the common purpose to provide practice guidelines in describing and quantifying radiologic findings and to minimize subjectivity. Moreover, the accurate and systematic classification of MRI using a standardized terminology of reporting creates reproducibility that is ideally reflected in high intra-and interrater reliability of each method.…”
Section: Discussionmentioning
confidence: 99%
“…So far, only a few studies have focused on the evaluation of MR-based hip scoring methods [24][25][26]; moreover, only one of these studies used the complete study cohort for correlation with surgical reports [26]. Overall, these studies showed a good performance evaluation hip MRI with surgical correlation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Arthroscopy represents the gold standard but is invasive, necessitates a general anaesthetic and is best reserved for patients in whom concomitant therapeutic intervention is to be undertaken. Much of the radiology literature has focused on the use of MR arthrography of the hip to detect labral and cartilage pathology [1][2][3][4][5]. A number of groups have also studied the role of non-contrast MRI in the detection of labral tears associated with femoroacetabular impingement and acetabular dysplasia [6][7][8][9].…”
mentioning
confidence: 99%